Lek habitat and behavior of the greater bird-of-paradise in South Papua, Indonesia - YENI A. MULYANI; ANI MARDIASTUTI; PUJI RAHAYU; MURTINI MURTINI (Society for Indonesian Biodiversity, 2025)
Abstract. Mulyani YA, Mardiastuti A, Rahayu P, Murtini. 2025. Lek habitat and behavior of the greater bird-of-paradise in South Papua, Indonesia. Biodiversitas 26: 5057-5066. The greater bird-of-paradise (Paradisaea apoda) is renowned for its extraordinarily beautiful display in its lek mating system. Given the threat posed by this endemic species from hunting and habitat conversion, a conservation effort is critical. However, data on its bio-ecology remain limited. This study aims to describe the characteristics of the lek tree and its surroundings as a lek habitat, and lek behavior, especially concerning the males on the lek trees during courtship display. The research was conducted in a post-logging timber concession company in South Papua in July 2023, through direct observations of behavior and the lek tree habitat. Two lek trees were identified, but observation was focused on one lek tree. The lek tree was a tall, emergent tree of Gironniera sp. (27 m, clear bole height 17 m; diameter 39.7 cm), surrounded by a dense tree canopy. The dominant trees in the lek site included Litsea firma, Vatica rassak, and Syzygium sp., with importance value indices of 41.79%, 31.33%, and 28.17%, respectively. The observation period at the lek tree spanned 7 days, totaling 303 minutes; lekking activity occurred from 6:00 am to 10:00 am and 2:00 to 4:15 pm. The behavior of the male birds could be categorized into arrival of a male host, arrival of other males, arrival of females, initiation of dance rituals by males, male selection by females, mounting and copulation, departure of females, and departure of males. Mounting was observed only twice by a single male. The males’ frequent loud calls during lekking make them highly detectable and prone to illegal hunting. The lek trees in this post-logging area indicated the importance of habitat management for species conservation. Protecting lek habitats by controlling logging operations and developing avitourism initiatives are important approaches to support the conservation of the greater bird-of-paradise and regional biodiversity in South Papua.